Clinical and Radiological Comparison of Unilateral Biportal Endoscopic and Percutaneous Transforaminal Endoscopic Discectomy in the Treatment of Lumbar Spinal Degenerative Disease - Hongtao Ding; Xiao Han; Yonggang Xing; Yajun Liu; Da He; Xiaoguang Han (Orthopaedic Surgery)
ABSTRACT Objective Unilateral biportal endoscopic discectomy (UBE) is an emerging and minimally invasive surgeryfor lumbar spinal degenerative disease. However, the efficacy, safety and the radiological changes of dural sac and paraspinal muscle of UBE compared with the conventional percutaneous transforaminal endoscopic discectomy (PTED) remains to be determined. The purpose of the study was to comprehensively compare the clinical efficacy between UBE and PTED in the surgical treatment of lumbar spinal degenerative disease. Methods The clinical and radiological data of patients who underwent single‐segment endoscopic surgery for lumbar spinal degenerative disease in our hospital from January 2021 to June 2022 were collected in the retrospective study. The visual analogue score (VAS) for back and leg pain, Oswestry disability index (ODI) before and 3, 6, and 12 months postoperative, changes of the cross‐sectional area of the dural sac area and paraspinal muscles on axial T2‐weighted MRI, operation time, intraoperative complications, MacNab criteria for evaluating efficacy at 12 months postoperatively, and recurrence rate of symptoms within 12 months were compared between patients undergoing PTED and UBE surgeries. Results A total of 142 patients were included. Among them 74 patients underwent PTED surgery, and 68 patients underwent UBE surgery. No statistically significant differences were identified between the groups in demographic variables. The average VAS and ODI scores in both groups showed significant improvement during the follow‐up but without statistically significant difference between the groups. The average operation time in the PTED group was 74.82 ± 19.49 min shorter than the 81.36 ± 21.37 min in the UBE group, exhibiting no statistically significant difference. Although the incidence of complications and recurrence was lower in the UBE group (4.05% vs. 1.47%, p = 0.354; 4.05% vs. 1.47%, p = 0.354, respectively), these differences did not reach statistical significance. The dural sac area in the PTED group increased byan average of 43.16 ± 14.62 cm2, and it was 68.53 ± 16.42 cm2 in the UBE group. Despite the dural sac area increased in both groups, the UBE group had a statistically significant greater improvement than the PTED group (p = 0.000). The area of the paraspinal muscle in the UBE group was significantly greater postoperatively (34.54 ± 2.75 cm2 vs. 36.22 ± 2.96 cm2, p = 0.001) and significantly less than in the PTED group at 12 months postoperatively (31.17 ± 2.59 cm2 vs. 29.46 ± 3.11 cm2, p = 0.001). Conclusion Both PTED and UBE surgeries can achieve satisfactory improvement in symptoms and function for patients with lumbar spinal degenerative disease and can be well‐maintained as a first‐line minimally invasive treatment. However, the UBE technique can achieve a better decompression area to restore the normal shape of the dural sac but may lead to greater paraspinal muscle damage and atrophy.